Dynamic evaluation of air quality models over European regions. (June 2015) - Thunis, P.; Pisoni, E.; Degraeuwe, B.; Kranenburg, R.; Schaap, M.; Clappier, A.
Abstract: Chemistry-transport models are increasingly used in Europe for estimating air quality or forecasting changes in pollution levels. But with this increased use of modeling arises the need of harmonizing the methodologies to determine the quality of air quality model applications. This is complex for planning applications, i.e. when models are used to assess the impact of realistic or virtual emission scenarios. In this work, the methodology based on the calculation of potencies proposed by Thunis and Clappier (2014) to analyze the model responses to emission reductions is applied on three different domains in Europe (Po valley, Southern Poland and Flanders). This methodology is further elaborated to facilitate the inter-comparison process and bring in a single diagram the possibility of differentiating long-term from short-term effects. This methodology is designed for model users to interpret their model results but also for policy-makers to help them defining intervention priorities. The methodology is applied to both daily PM10 and 8 h daily maximum ozone. Highlights: Air quality model responses to emission reduction scenarios are presented. Maximum potential for local emission abatement is identified. Relative importance of the various precursor emissions is assessed. Degree of non-linearity of the model responses is estimated. Three case studies in Europe are considered.